Modeling and observations of dissolved oxygen content in the Lake Teletskoye - Aleksandr T. Zinoviev; Konstantin B. Koshelev; Aleksandr V. Dyachenko (Водное хозяйство России: проблемы, технологии, управление)
The Lake Teletskoye is a unique water body in Western Siberia. The oxygen regime of Lake Teletskoye is an indicator characterizing the state of the reservoir. Assessing its changes due to possible anthropogenic intervention is extremely important.